Vanadium (V) bio-detoxification based on washing water of rice as microbial and carbon sources - Hao, Liting; Wang, Xinli; Shi, Jinkai; Li, Lin; Hao, Xiaodi (Frontiers in Environmental Science, 2023)
Mining and smelting result in vanadium (V) being released into the environment. Biologically removing V(V) with washing water of rice (WWR) was investigated in this study. Over a 7-d trial, the V(V) removal efficiency increased with dosing washing water of rice dosage up to 56.6%. The results demonstrated that washing water of rice could be used as carbon and microbial sources for biologically reducing V(V). Using domesticated sludge as the inoculum could enhance V(V) detoxification performance, and 95.5% of V(V) was removed in the inoculated system for 5 d. Soluble V(V) was transformed into insoluble V(IV) (VO2), which could be further removed with precipitation. In addition to ABC transporters, a two-component system was also involved in V(V) reduction. The study confirmed that washing water of rice could be utilized for V(V) bio-detoxification.